Effect of enamel matrix derivative on bone formation around intraosseous titanium implant: An experimental study in canine model - Reza Birang; Mohammad Shahabooei; Fatemeh Mashhadiabbas; Mehdi Atabaki; Narges Naghsh; Keikavous Kavosh; Ehsan Birang; Ahmad Mogharehabed (Wolters Kluwer Medknow Publications, 2012)
Background: The purpose of this study was to perform a histological, histomorphometrical, and immunohistochemical evaluation of the effect of Enamel matrix derivative (EMD) on bone formation around titanium dental implant. Materials and Methods: In this animal study, 12 implants (10 × 3.8 mm) were inserted in the tibia bone of three dogs of Iranian breed. Two implants were placed in each tibia with EMD only on the left side. The dogs were sacrificed 2, 4, and 6 weeks after implantation. Following decalcification of the implants' surrounding tissue and preparation of 4 μm thick sections, they were stained with hematoxylin and eosin (H and E) and immunohistochemical (IHC) stain for osteopontin (OPN) marker. Histomorphometric evaluation was performed via measurement of the percentage of the woven, lamellar, and total generated bone. Light microscopy osteoblastic intensity of OPN in osteoblasts and bone matrix was also evaluated Data were analyzed by Wilcoxon signed Ranks, and Mc Nemar tests. Results: In both control and EMD-applied groups, bone formation was recognized around the implants at the 4 th week postimplantation. The percentage of total generated bone in the test group was higher than the control group, although being not statistically significant (P value = 0.917). Osteoclasts exhibited significantly higher proliferation activity compared the control group when stimulated by EMD (P value = 0.027). On average, the staining intensity in osteoblasts and extracellular matrix of bone, in EMD-applied subjects was higher than those of the controls (P value = 0.167 and P value = 0.414, respectively). Conclusion: EMD enhanced bone formation around dental implants, but this increase was not significant.